Rheology Analysis of 3D Printed Geopolymer Based on High Calcium Fly Ash - Tajunnisa, Yuyun; Arrafid, Rifqi Nadhif; Bayuaji, Ridho; Nurhadi, Hendro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The advancement of 3D concrete printing has focused on automation research in recent decades. 3D printing technology is adequate to reduce waste and improve efficiency for construction. Former research on 3D concrete printing used hydration cement based on ordinary Portland cement (OPC), which was not environmentally friendly. An alternative material to overcome problems with hydrated cement mortar is a geopolymer. Geopolymer mortar based on 3D printing is still in its infancy. Mechanical and rheological properties are the key parameters of this technology: yield stress, shear stress, and viscosity. The flow characteristics of 3D concrete printing represented the ability of material transfer along the system of the 3D printing machine. This research utilizes type C fly ash waste as the primary material for making geopolymer 3D-printed concrete. Variations of 8, 10, and 12 M of NaOH concentration were used to investigate the relationship between workability and quality of the geopolymer mortar. Workability testing of 3D concrete printing consists of several parameters: pumpability, extrudability, and buildability. Material identification, including rheology and flowability, is carried out to determine mortar specimens' pumpability, extrudability, and buildability. Several test approaches, such as slump flow, slump, shape retention, and rheometer tests using the vane shear approach method, were conducted to identify the rheological characteristics and flowability of the material. Based on testing of the material's workability, 10 M NaOH concentration variation is the most suitable material for future 3D printing material. The workability of 10 M NaOH is 177.5 mm and the the copressive strength is 25.84 Mpa. This variation meet ACI 318/318R – 14 criterion for building structure.